Cytokine signaling defects in primary atopic diseases—an updated review - Thakur, Vaishali; Pilania, Rakesh Kumar; Sharma, Arunima; Sharma, Saniya; Mario, Alfred Thomas; Goyal, Taru; Sharma, Madhubala; Vaitheeswaran, Gayathri Coimbatore; Vignesh, Pandiarajan; Singh, Surjit; Dhaliwal, Manpreet; Rawat, Amit (Frontiers in Allergy, 2025)
Primary atopic disorders (PADs) are monogenic conditions associated with severe, early-onset atopic diseases. Clinically, they often overlap with polygenic allergic conditions, making specialized laboratory testing necessary to distinguish them from polygenic atopy. Multisystem involvement, such as growth failure, recurrent infections, and autoimmunity, points towards PADs warranting further investigations. PADs associated with immune dysregulation can be broadly categorized into four mechanistic groups: those affecting the regulation of cell cytoskeleton dynamics, T-cell receptor (TCR) signaling and repertoire diversity, and function of regulatory T cell (Treg), and cytokine signaling. In this review, we have examined the defects in cytokine signaling pathways associated with PADs. Key cytokine signaling pathways implicated in PADs include the STAT3, JAK1/STAT5b, and TGF-β pathways. Pathogenic variants in these pathways result in complex clinical phenotypes but share a common theme of Th2 polarization and severe atopic manifestations. Early and accurate differentiation between polygenic atopy and PADs is crucial, as it allows for timely, targeted immunological or genetic interventions that may significantly improve patient outcomes.